PEMBERDAYAAN KELUARGA MENGHADAPI PADEMI COVID 19 DENGAN PENANAMAN DAN PEMANFAATAN TANAMAN OBAT KELUARGA DI KELURAHAN DEGAYU KECAMATAN PEKALONGAN UTARA - Dwi Edi Wibowo; Beny Diah Madusari; Arum Ardianingsih (PENA ABDIMAS : Jurnal Pengabdian Masyarakat, 2020)
Indonesia is also affected by the virus, so there is a need for family resilience to stem the covid virus 19. One of the programs that can be implemented by families in efforts to improve welfare, especially in the food sector is the planting and utilization of Family Medicinal Plants (TOGA). One program that can be implemented by families in efforts to improve health, especially in the field of medicine is the planting and utilization program of Family Medicinal Plants (TOGA). Method of training, One of the programs that can be implemented by families in efforts to improve welfare, especially in the field of food is a planting and utilization program for Family Medicinal Plants (TOGA). This activity was at the same time addressing the decline in people's purchasing power due to the pandemic covid 19 which caused the price of drugs to become more expensive, so that it indirectly had an impact on the declining degree of public healthKeywords: empowerment, family medicinal plants, covid 19